lim(x->0)((1-e^2x)/(1-e^x))

2 Answers | Add Yours

rcmath's profile pic

rcmath | High School Teacher | (Level 1) Associate Educator

Posted on

`lim_(x->0)[1-e^(2x)]/[1-e^x]=`

`lim_(x->0)[(1-e^x)(1+e^x)]/(1-e^x)=`

`lim_(x->0)1+e^x=`

`1+1=2`

 

zainabalaswad's profile pic

zainabalaswad | High School Teacher | eNotes Newbie

Posted on

otner solution:

By L'Hôpital's rule we get:

lim as x goes to 0 (  -2e^2x / - e^x )  =

lim as x goes to 0 ( 2e^x ) = 2

We’ve answered 315,839 questions. We can answer yours, too.

Ask a question